Motivic p-adic tame cohomology - Merici, Alberto (Bulletin of the London Mathematical Society, 2025)
We construct a comparison functor between (A(1)-local) tame motives and ((sic)-local) log-etale motives over a field of positive characteristic. This generalizes Binda-Park-Ostv ae r's comparison for the Nisnevich topology. As a consequence, we construct an E-infinity-ring spectrum Hz/p(m) representing mod p(m) tame motivic cohomology: the existence of this ring spectrum and the usual properties of motives imply some results on tame motivic cohomology and a comparison with log & eacute;tale motivic cohomology.